Teaching at the basic level in Mexico: from professionalization to precarius position - Alaníz Hernández, Claudia (2018)
The objective of this article is to analyze the impact of the educational reform implemented by President Peña Nieto in the exercise of teaching at the basic level as a professional activity. Methodologically, Hortal's (2002) proposal on the ethics of the professions is used as an analysis element to argue how this reform of 2013 is a watershed part in the conception of the teaching profession as a state profession. The study of the working conditions of the teachers allows us to conclude that, paradoxically, the changes place teachers in a precarius position, by individualizing the activity, instead of strengthening the professionalization of the teachers of basic education.